Craniocervical manual lymphatic drainage and its impact on intracranial pressure – a pilot study. (30th May 2016) - Roth, C.; Stitz, H.; Roth, C.; Ferbert, A.; Deinsberger, W.; Pahl, R.; Engel, H.; Kleffmann, J.
Abstract : Background and purpose: Theoretical considerations and the results of animal studies indicate that manual lymphatic drainage (MLD) might have an impact on intracranial pressure (ICP). There is a lack of clinically qualitative investigations on patients with severe cerebral diseases. Methods: Between April 2013 and January 2015 a prospective observational study was performed on patients who were undergoing intracranial pressure measurement and treatment with MLD. ICP, cerebral perfusion pressure, mean arterial pressure (MAP), heart rate and oxygen saturation were recorded continuously 15 min before the procedure, during MLD (22 min) and for 15 min after the procedure. For analysis the data treatment units were divided into two groups: patients with a mean baseline ICP <15 mmHg (group 1) and patients with a mean ICP ≥15 mmHg before MLD (group 2). Results: A total of 133 treatment units (61 patients) were analysed (group 1 n = 99; group 2 n = 34). The mean baseline ICP was 10.4 mmHg overall, and 8.3 mmHg and 18.6 mmHg respectively in group 1 and group 2; ICP significantly decreased during therapy with MLD and this persisted during the follow‐up period in group 2. MAP did not show any significant differences between the different periods. Conclusions: Our data showed a significant reduction of ICP during therapy with craniocervical MLD in patients with severe cerebral diseases.